Data of worldwide observational studies of adults with accelerometry-measured physical activity and sedentary behavior - Kelly R. Evenson; Elissa Scherer; Carmen C. Cuthbertson; Kennedy M. Peter-Marske; Gabriel J. Madson; Stephanie Eckman (Data in Brief, 2023)
A compendium of observational studies of adults that collected accelerometry to assess physical activity and sedentary behavior (i.e., physical behaviors) could facilitate cross-study comparisons, meta-analyses, and future research collaborations. Therefore, we performed a systematic search to identify observational studies, including surveillance systems, that collected accelerometry-measured physical activity and sedentary behavior among adults. We performed a search using PubMed, Web of Science, and SPORTDiscus for studies published on or before June 1, 2021. After screening 5686 abstracts and 1027 full text articles, we included 155 unique studies that collected accelerometry on at least 500 adults 18 years or older. Most studies used one accelerometer (n=146), although eight studies used two accelerometers and one study used four accelerometers. The country of data collection, age range, and accelerometer characteristics were abstracted and checked by a second reviewer. These datasets summarizing relevant observational studies of adults can be a resource to researchers seeking to identify data sources for accelerometer-measured physical activity and sedentary behavior from around the world.